Gravis defectus discretionis iudicii w opublikowanych wyrokach Roty Rzymskiej z 2005 r. Część II - Góralski, Wojciech (Ius Matrimoniale, 2014)
A serious lack of evaluative discernment, as regards essential marital rights and obligations arises from a serious disruption of a cognitive, critical, evaluative, consideration act or an act regarding choice – as regards essential marital rights and obligations. As far as intellectual acts are concerned, a serious lack of evaluative discernment results in dysfunctions of cognitive and critical acts, that is evaluative ones, which prevent from correct cognition and proper evaluation of essential marital rights and obligations; as regards an act of will, its lack results from dysfunction of volitional act, which destruct freedom of choice. In proving a serious lack of evaluative discernment as far as essential marital rights and obligations are concerned, all evidence determined in CIC and Dignitas connubii Instruction are used, and the Rota decrees give the greatest attention to direct evidence, which are evidence of experts.